The kinetics and mechanism of filiform corrosion occurring on zinc-aluminium-magnesium coated steel - Natalie Wint (Corrosion Science, 2019)
This paper describes a systematic study into the initiation and propagation of filiform corrosion (FFC) on industrially important Zinc-Aluminium-Magnesium (ZAM) alloy coatings for steels. An artificial scribe defect is created in model organic coatings applied to ZAM. Corrosion is initiated using HCl, NaCl, FeCl2 and acetic acid. Only acetic acid is able to reproducibly initiate FFC. The FFC (area) rate is shown to be proportional to the amount of acetic acid introduced. The FFC mechanism is explained in terms of the relative susceptibility of alloy phases to anodic dissolution, determined using scanning electron microscopy and scanning Kelvin probe force microscopy.